2021
DOI: 10.3389/fcimb.2021.676638
|View full text |Cite
|
Sign up to set email alerts
|

MoWa: A Disinfectant for Hospital Surfaces Contaminated With Methicillin-Resistant Staphylococcus aureus (MRSA) and Other Nosocomial Pathogens

Abstract: IntroductionStaphylococcus aureus strains, including methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA), are a main cause of nosocomial infection in the world. The majority of nosocomial S. aureus-infection are traced back to a source of contaminated surfaces including surgery tables. We assessed the efficacy of a mixture of levulinic acid (LA) and sodium dodecyl sulfate (SDS), hereafter called MoWa, to eradicate nosocomial pathogens from contaminated surfaces.Methods and Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…The MRSA strains included in this study showed resistance profiles similar to those of clinical isolates circulating in hospital settings in Colombia [ 30 , 31 ]. S. aureus , including MRSA strains, has been reported to be one of the leading causes of nosocomial infections worldwide, especially among patients in surgery, undergoing hemodialysis, and in ICU units, because of the long-term use of venous and urinary catheters [ 32 , 33 , 34 ]. The surfaces of some items in these units, such as beds, operating tables, infusion pumps, and electrocardiography devices, among others, have been found to be contaminated with MRSA strains, which could lead to cross-contamination via the hands of healthcare personnel [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MRSA strains included in this study showed resistance profiles similar to those of clinical isolates circulating in hospital settings in Colombia [ 30 , 31 ]. S. aureus , including MRSA strains, has been reported to be one of the leading causes of nosocomial infections worldwide, especially among patients in surgery, undergoing hemodialysis, and in ICU units, because of the long-term use of venous and urinary catheters [ 32 , 33 , 34 ]. The surfaces of some items in these units, such as beds, operating tables, infusion pumps, and electrocardiography devices, among others, have been found to be contaminated with MRSA strains, which could lead to cross-contamination via the hands of healthcare personnel [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here, special attention should be given to the resistance of A. baumannii biofilms to commercial disinfectants [ 16 ]. The need for the identification of novel disinfectant compounds to treat resistant pathogens, such as A. baumannii , has been recognized and emphasized [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although septic poisoning occurs mostly after serious operation, among immunocompromised patients and elderly convalescents particularly with chronic health conditions, the main reason of infections is insufficient disinfection. Apart from the above-mentioned germs causing COVID-19 co-infections, one must notice the nosocomial pathogens from high-touch environmental surfaces (door handles, bed rails, and protective barriers) and medical devices (thermometers, stethoscopes) such as methicillin-resistant S. aureus , Clostridium difficile , vancomycin-resistant Enterococcus and Acinetobacter species [ 43 , 44 ]. Moreover, some products used by patients, such as mobile phones, are significantly more contaminated than other items, and thus generally considered as microbiologically polluted [ 45 ].…”
Section: Applications Of Photocatalysis Against Co-pathogens Of Covid...mentioning
confidence: 99%